Strategi Guru dalam Menciptakan Sekolah Ramah Anak - Sari, Inda (Journal of Innovation in Teaching and Instructional Media, 2025)
This research aims to explore the strategies implemented by teachers in creating child-friendly schools. The main focus of this research is to identify various efforts made by teachers, the obstacles they face, and the solutions developed to address the challenges in realizing a school that is truly responsive to the needs and rights of children. The research method used is a qualitative case study, with data collection through in-depth interviews, observations, and document reviews at selected elementary schools. The main participants in this study are teachers, school principals, and representatives of parents. The research results show that teachers have implemented various strategies to create child-friendly schools, such as: (1) Creating a safe, comfortable, and supportive learning environment for children’s development; (2) Developing a curriculum that is responsive to children’s rights; (3) Implementing interactive and student-centered learning methods; and (4) Establishing good cooperation with parents and the community. However, in its implementation, teachers also face several obstacles, such as limited facilities, high workloads, and some parents who still do not understand the concept of child-friendly schools. The school has been striving to overcome these obstacles through: (1) Optimizing the use of existing facilities; (2) Training and mentoring for teachers; and (3) Actively involving parents in school activities.